Information Systems Assessment as a Learning Process - Etzerodt, Preben; Madsen, Kim Halskov (DAIMI Report Series, 1988)
In this paper we emphazise the cognitive and learning aspects of information systems assessment. In doing so we step away from what we consider as the conventional frame work. We elucidate the cognitive and learning aspects by presenting a specific project on information systems assessment. In this project the basic means for fostering a learning process among the participants have been: working groups, focusing on experiences gained by individuals using the information system, using unstructured descriptions to clarify and interpret situations and using specific techniques to uncover and contrast different framings of situations in the organization.